Youth Ethnic and National Identity in Bosnia and Herzegovina - Majstorovic, Danijela. author. aut Link
XI, 245 p.
Keywords: Youth Ethnic and National Identity in Bosnia and Herzegovina is an interdisciplinary effort to position and describe the contested nature of state and ethnic identity among youth in Bosnia and Herzegovina by providing empirical, first-hand evidence on identity structure and the subsequent implications for inter-group relations.